Evaluation of the versatility of tannases produced from Aspergillus niger and Penicillium variable with respect to gallic acid production, gallate ester synthesis, animal feed improvement, tannery effluent degradation and tannin stain removal - Sharma, Shashi; Saxena, R. K. (Research in Biotechnology, 2012)
The potentiality of tannases produced from A. niger and P. variable were investigated with respect to gallic acid production, synthesis of gallate esters, animal feed improvement, tannery effluent degradation and tannin stain removal. Titrimetry results showed significant gallic acid production with 92 % conversion of 8 % tannic acid catalyzed by lyophilized A. niger tannase and 60 % conversion of 3 % tannic acid by lyophilized P. variable tannase in 8h. In gallate ester synthesis, esterfication rate was observed to be affected by the substrate molar ratio and temperature with maximum at 50◦C. Amongst the various organic solvents evaluated, n-hexane (log P 2.0) promoted maximum synthesis of both methyl gallate (MG) and propyl gallate (PG). Also low initial water activity (aw) of 0.11 – 0.33 obtained with LiCl2 and MgCl2.2H2O gave better yields for both MG and PG and by both tannases. Furthermore, addition of molecular sieves at 0h in esterification reaction resulted in enhanced conversion of gallic acid and methanol into methyl gallate (90.7 % and 83 %) by A. niger and P. variable tannase respectively. Similarly, 94.8 % and 89.6 % conversion of gallic acid and propanol into propyl gallate was achieved by A. niger and P. variable tannase after addition of molecular sieves at 0h. In the hydrolysis of xylan and pectin, A. niger tannase showed outstanding result by efficiently degrading them and producing ferulic acid at retention time of 75.90 min. Besides this, both A. niger and P. variable tannases showed considerable degradation of 15 X diluted tannery effluent i.e. 45 and 36 % in 48 h respectively. In the removal of tea / tannin stains, the increase in temperature from 37◦C to 50◦C showed 15 % increase in reflectance for A. niger tannase and 21 % for P. variable tannase indicating its potential use in tannin stain remover (Tannosol).